PENGARUH FEE AUDIT, FINANCIAL DISTRESS, KOMISARIS INDEPENDEN, DAN KOMITE AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN - Lestari, Sari; Shanti, Yunita Kurnia (JURNAL PUNDI, 2024)
This research aims to examine the influence of audit fees, financial distress, independent commissioners and audit committees on the integrity of financial reports. Audit fees are measured using the natural logarithm of professional fees, financial distress is measured using the debt to equity ratio, independent commissioners are measured using the ratio of the number of members of the company's independent commissioners to the number of members of the company's board of commissioners, audit committees are measured using the comparison of the number of audit committees that come from from the independent committee with the number of audit committee members and the integrity of the financial reports as measured using the market to book ratio. This type of research is quantitative. Based on purposive sampling, the number of sample companies was 29 companies with an observation period of 5 years, so the total sample was 145 data on the property and real estate sectors listed on the Indonesia Stock Exchange (BEI) during the 2018-2022 period. The data analysis used in this research is a panel data regression model using E-Views 12. The results of this research show that partially audit fees and audit committees have no effect on the integrity of financial reports. Financial distress and independent commissioners have a significant effect on the integrity of financial reports. Meanwhile, simultaneously audit fees, financial distress, independent commissioners and audit committees influence the integrity of financial reports. Keywords: Financial Statement Integrity, Audit Fees, Financial Distress, Independent Commissioner, Audit Committee.